2005
DOI: 10.1093/aob/mci116
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Plastic Responses to Defoliation due to Variation in the Timing of Treatments for Two Species of Sesbania (Fabaceae)

Abstract: While there were effects of timing of defoliation and differences between species, the nature of these effects did not precisely fit our predictions. Our results suggest that differences in the length and flexibility of the life cycles of the two species allowed for unexpected variation in responses. For example, because flower production continued after the last treatment in S. vesicaria, responses were not constrained to reductions in individual seed mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…Support for the hypothesis that tolerance to defoliation in annuals increases from the vegetative rosette stage to the reproductive stage has previously been obtained in greenhouse experiments with A. thaliana [33] but see [28], Plantago aristata [17], Raphanus sativus [16], Sesbania macrocarpa and S. vesicaria [15], and in a field study of Ipomoea purpurea [13]. In contrast, no evidence of an ontogenetic increase in tolerance to defoliation was observed in a greenhouse experiment with Senecio vulgaris [34], or in a field study of Cucurbita pepo [35].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Support for the hypothesis that tolerance to defoliation in annuals increases from the vegetative rosette stage to the reproductive stage has previously been obtained in greenhouse experiments with A. thaliana [33] but see [28], Plantago aristata [17], Raphanus sativus [16], Sesbania macrocarpa and S. vesicaria [15], and in a field study of Ipomoea purpurea [13]. In contrast, no evidence of an ontogenetic increase in tolerance to defoliation was observed in a greenhouse experiment with Senecio vulgaris [34], or in a field study of Cucurbita pepo [35].…”
Section: Discussionmentioning
confidence: 66%
“…There is some support for the predictions that leaf damage early in the season is more detrimental than damage late in the season, e.g. [13], [15], [16], and that the components of fitness most affected by herbivory shift along ontogeny in annual plants [17]. However, because responses to herbivory may often be context-dependent [7], [9], [11] and most studies of seasonal changes in tolerance to leaf herbivory have been conducted in the greenhouse rather than in the field, e.g.…”
Section: Introductionmentioning
confidence: 88%
“…The majority of these studies reported detrimental effects on components of plant fitness, such as reduced shoot and root biomass (Knapp 1986;Quinn and Hall 1996;Wirf 2006), decreased flower, fruit, or seed production (Obeso 1993;Domínguez and Dirzo 1994;Koptur et al 1996;Genter et al 1997), and decreased seed size (Sackston 1959;Rockwood 1973;Koptur et al 1996). On the other hand, some studies have demonstrated compensatory or even beneficial, overcompensatory effects of herbivory (McNaughton 1983;Karban and Myers 1989;Paige 1994;Lennartsson et al 1998;Marshall et al 2005; but see Belsky 1986 andBelsky et al 1993) or variable effects, depending on whether defoliation occurred naturally or was achieved artificially (Gedge and Maun 1992;Nowatzki and Weiss 1997). For example, in wild radish, Raphanus raphanistrum, artificial clipping of leaves by scissors resulted in only minimal induced plant resistance (e.g., increased production of defensive chemicals) (Agrawal 1999(Agrawal , 2000a, whereas strong induced resistance, no induced resistance, or even induced susceptibility to herbivory occurred following attack by four lepidopteran herbivores (Agrawal 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of herbivory are dependent upon a number of factors, including the extent of plant tissue damage (Obeso and Grubb 1994;Koptur et al 1996;Quinn and Hall 1996;Susko and Lovett-Doust 1999), the developmental stage of a plant at the time of assault (Hare 1980;Obeso and Grubb 1994;Escarré et al 1996;Lennartsson et al 1998;Marshall et al 2005), prevailing environmental conditions when herbivory occurs (Lee and Bazzaz 1980;Maschinski and Whitham 1989;Escarré et al 1996;Mabry and Wayne 1997), and the type of plant tissue (i.e., leaves, meristems, reproductive structures, roots, etc.) removed (Escarré et al 1996;Quinn and Hall 1996;Susko and Lovett-Doust 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Resources might be limited either by the plant's capacity to utilise the available resources, or simply by low resource availability per se. It is also likely that (over-) compensatory growth is determined by the timing of damage (Lennartsson et al, 1998;Marshall et al, 2005). The accumulation of storage nutrients in rosettes of C. dubium was probably not sufficient by June when the mowing has occurred.…”
Section: Effects Of Mowingmentioning
confidence: 99%